The Effect of Movement on Cognitive Performance - Mualem, Raed; Leisman, Gerry; Zbedat, Yusra; Ganem, Sherif; Mualem, Ola; Amaria, Monjed; Kozle, Aiman; Khayat-Moughrabi, Safa; Ornai, Alon (Frontiers in Public Health, 2018)
The study examines the relationship between walking, cognitive, and academic skills. Students from elementary, middle, high school, and college were required to walk for 10 min prior to completing feature detection, Simon-type memory, and mathematical problem-solving tasks. Participants were counterbalanced to remove a time bias. Ten minutes of walking had a significant positive effect on Simon-type memory and critical feature-detection tasks among all age groups. Separately, with mathematical problem-solving ability, higher performing high-school students demonstrated significant positive effects on mathematical reasoning tasks based on the Bloom Taxonomy. However, poorly achieving high-school students performed significantly better than those with higher grades in mathematics on tests of mathematical problem-solving ability based on the Bloom’s Taxonomy. The study indicates that there is justification to employ relatively simple means to effect lifestyle, academic, and cognitive performance.